2022
DOI: 10.1101/2022.08.10.503439
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genetic variation associated with relative resistance in teak (Tectona grandis L. f.) against the leaf skeletonizer, Eutectona machaeralis Walker

Abstract: Background: Photosynthesizing tissue of teak (Tectona grandis L. f.) foliage is damaged by a host-specific insect pest called leaf skeletonizer (Eutectona machaeralis Walker) that severely eclipses annual growth increment and carbon sequestration of natural populations and plantation of teak. Gene-assisted selection of relatively resistant teak clones may efficiently control the damage in the populations and plantations. The present investigation aimed to identify genetic variation associated with relative res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 54 publications
0
1
0
Order By: Relevance
“…In addition to its adaptability to a wide range of climatic conditions, teak also has a high tolerance to soil variations and can grow in a variety of soil types, including well-drained sandy, loamy, and clay soils [ 2 ]. Studies have also found that different teak genotypes have high levels of resistance to insect pests and diseases, making it a suitable option for sustainable forestry practices [ 6 ]. Overall, the versatility and resilience of teak make it an attractive option for both commercial and conservation purposes.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to its adaptability to a wide range of climatic conditions, teak also has a high tolerance to soil variations and can grow in a variety of soil types, including well-drained sandy, loamy, and clay soils [ 2 ]. Studies have also found that different teak genotypes have high levels of resistance to insect pests and diseases, making it a suitable option for sustainable forestry practices [ 6 ]. Overall, the versatility and resilience of teak make it an attractive option for both commercial and conservation purposes.…”
Section: Introductionmentioning
confidence: 99%